Natural Dyes Extraction of Curcuma Longa, Tradescantia Spatacea, and Bryophyta Absorption Capability on TiO2 Nanofiber Thin Layer: Novita Asma Ilahi, Fadillah Hazrina, Afrizal Abdi Musyafiq, Ahmad Aftah Syukro, Erliza Septia Nagara - Novita Asma Ilahi Novita Asma Ilahi; Fadillah Hazrina Fadillah Hazrina; Afrizal Abdi Musyafiq Afrizal Abdi Musyafiq; Ahmad Aftah Syukron Ahmad Aftah Syukron; Erliza Septia Nagara Erliza Septia Nagara (Jurnal Fisika dan Aplikasinya, 2023)
Exploration of plant variations is required to determine the absorbance ability and potential utilization of dye in the development of Dye-Sensitized Solar Cells (DSSC). Extraction of four different plants was carried out to obtain three different types of natural dyes. The curcumin dye was obtained from the extraction of Curcuma longa, the chlorophyl dye was obtained from the extraction of Bryophytes, the anthocyanin dye was obtained from the extraction of Brassica oleracea var capitata f. rubra, and Tradescantia spathacea. The research was conducted to determine the absorbance capability of each different type of dye and the image of the thin layer of TiO2 nanofiber used by DSSC. Extraction is carried out through a drying and pounding process. The powder of each plant was then synthesized using ethanol through a homogenization process for 12 hours. The research utilizes a spectrophotometer UV-Visible to determine the wavelength of the natural dye, as well as a scanning electron microscope (SEM) to determine the size of the titanium dioxide (TiO2) thin film nanofiber based on the displayed image. DSSC utilizes TiO2 nanofiber as a thin layer of semiconductor. The dye absorption peak is in the wavelength range of 350-500 nm and 650-700 nm. Based on the analysis of absorbance results, curcumin dye has the greatest potential to be used in DSSC with the highest absorption ability in all its occurrences at visible light wavelengths.